2013
DOI: 10.1038/cddis.2013.80
|View full text |Cite
|
Sign up to set email alerts
|

Secreted calmodulin-like skin protein inhibits neuronal death in cell-based Alzheimer’s disease models via the heterotrimeric Humanin receptor

Abstract: Humanin is a secreted bioactive peptide that is protective in a variety of death models, including cell-based neuronal death models related to Alzheimer's disease (AD). To mediate the protective effect in AD-related death models, Humanin signals via a cell-surface receptor that is generally composed of three subunits: ciliary neurotrophic factor receptor α, WSX-1 and gp130 (heterotrimeric Humanin receptor; htHNR). However, the protective effect of Humanin via the htHNR is weak (EC50=1–10 μℳ); therefore, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 46 publications
1
44
0
1
Order By: Relevance
“…CLSP inhibits both the APP-mediated neuronal cell death (21,24) and the UNC5C-mediated neuronal cell death (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CLSP inhibits both the APP-mediated neuronal cell death (21,24) and the UNC5C-mediated neuronal cell death (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Purified GST-mCLSP1-MycHis, bound to Glutathione-Sepharose (GE Healthcare), was co-incubated in PBS containing thrombin (1 unit/ml, GE Healthcare) at 25°C overnight to be released from GST that bound to the glutathione-Sepharose, as shown previously (21). Recombinant GST protein was also purified for the usage as a negative control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This inhibitory effect is mediated via binding of Humanin to its heterotrimeric receptor (htHNR), which is composed of gp130, ciliary neurotrophic factor receptor a, and WSX-1 [5]. A recent study showed that secreted calmodulin-like skin protein (CLSP) is a physiological agonist of the htHNR that is 10 5 fold more potent than Humanin and suggested that CLSP, rather than Humanin, plays a central role in inhibiting neuronal cell death in vivo [6].…”
Section: Introductionmentioning
confidence: 98%